Reproduction of Pratylenchus penetrans on various rotation crops in Quebec - Bélair, G.; Fournier, Y.; Dauphinais, N.; Dangi, O.P. (Phytoprotection, 2002)
The reproduction of the root-lesion nematode Pratylenchus penetrans was assessed on 12 rotation crops under greenhouse conditions. Brown mustard (Brassica juncea) was the best host and increased the initial population by 17.2 times. Soybean (Glycine max), Japanese millet (Echinochloa frumentacea), rape (B. napus), buckwheat (Fagopyrum esculentum), white mustard (B. hirta), and perennial ryegrass (Lolium perenne) were also very efficient in multiplying the nematode and were not significantly different from rye (Secale cereale), a standard host crop. Foxtail millet (Setaria italica), oats (Avena sativa), corn (Zea mays), and bromegrass (Bromus inermis) increased the initial population by 5.8, 5.7, 4.5, and 3.2 times respectively, but significantly less than rye. Forage pearl millet (Pennisetum glaucum) was the poorest host with a reproduction rate of 0.4. These results indicate that most commonly recommended rotation crops are suitable for the build up of P. penetrans populations in the soil with the exception of forage pearl millet. This annual crop has a great potential as a rotation crop for controlling the root-lesion nematode in Quebec.